Acute effects of strength training interventions on subjective, neuromuscular, and biochemical fatigue parameters in elite youth soccer players - Kadlubowski, B.; Keiner, M.; Wirth, K.; Csapo, R. (Frontiers in Sports and Active Living, 2026)
This study examined acute neuromuscular, biochemical, and subjective fatigue responses to two strength training protocols—back squats with calf raises vs. back squats with plyometric exercises—in elite youth soccer players. The aim was to track the progression and resolution of fatigue over a 72 h recovery period and evaluate the practical feasibility of both protocols within high-performance training schedules. Thirty-two male athletes from a national youth elite training center participated in a crossover-controlled study. Each player completed both interventions, separated by an 8-day washout period. A comprehensive test battery assessed neuromuscular performance via the countermovement jump (CMJ), drop jump, isometric mid-thigh pull, adductor squeeze, and sit-and-reach test; biochemical markers via creatine kinase (CK); and subjective markers using the Hooper Index, visual analog scale (VAS), and session rating of perceived exertion (sRPE). Measurements were taken at baseline and 24, 48, and 72 h post-exercise. No significant interaction effects (training modality × time) were found (p > 0.05), indicating comparable fatigue and recovery trajectories for both protocols, whereas significant main effects of time were observed across all parameters, including CMJ [F(3,26) = 29.373, p < 0.001, n2 = 0.772] and CK [F(3,26) = 51.504, p < 0.001, n2 = 0.856]. Fatigue peaked between 24 and 48 h post-exercise and returned to baseline by 72 h. Subjective fatigue (Hooper, VAS) mirrored objective markers. Both traditional and reactive strength training induced short-term fatigue that resolved within 72 h, supporting their safe implementation in elite youth training programs, provided adequate recovery is allowed between sessions.